Incidental pulmonary nodules: What should we do in 2026? - Schmid-Bindert, Gerald; Vogel-Claussen, Jens; Bollmann, Benjamin-Alexander; Lamché, Joana; Eichhorn, Martin E.; Herth, Felix (Respiration, 2025)
Background: Incidental pulmonary nodules (IPNs) detected during routine thoracic CT scans offer a promising opportunity to shift lung cancer (LC) diagnoses toward earlier, more curable stages across a broad patient population. Despite their high potential to reduce LC-related mortality, the complexity and heterogeneity of existing guidelines, combined with inefficient follow-up processes, continue to limit the diagnostic and therapeutic benefits of IPN detection. Summary: This article examines the systemic barriers to effective IPN management and outlines strategic solutions, including automation and structured workflows as well as standardized patient communication. With the recent implementation of national lung cancer screening (LCS) programs, new opportunities arise to synergize infrastructures and optimize pulmonary nodule management within a unified framework. Key Message: Therefore, a clearer understanding of how IPNs should be managed - and how they can be integrated into broader early detection strategies - is essential for a truly holistic approach to early LC detection.